Main psychometric evaluation methods of measuring instruments reliability - Cunha, Cristiane Martins (2016)
Introduction: Literature has focused on the importance of proper psychometric evaluation of measuring instruments as a criterion for the good quality of the instrument in relation to evidence of validity and reliability. To assess the reliability is the first step to know the accuracy of a measuring instrument. Objective: This article presents the basic principles of psychometric evaluation of the reliability of measuring instruments and the main statistical methods described in the literature. Method: The survey was conducted from publications in Medline, LILACS, and IBECS databases and also from the descriptions in books regarding the field of study. The analysis of the studies involved reading titles, abstracts, and articles published in the last 10 years and excluded articles that were duplicated or not corresponding to the purpose of this review. Results: The main evaluation of reliability methods are based on the correlation between the items and internal consistency. The main methods based on correlations are the test-retest reliability, reliability from equivalent (or parallel) forms, and the reliability between observers; on the other hand, the main evaluation methods for internal consistency are the split-half method, the alpha correlation coefficient (Cronbach’s alpha) and the Kuder-Richardson formula. Conclusions: In general, the authors agree with the basic criteria for evaluating the reliability of a good measurement instrument. Reliability is a psychometric attribute needed in a good measurement instrument and needs to be covered in these study categories.